Systematic Surgical Approach to Alar Base Surgery in Rhinoplasty. Issue 6 (December 2020) - Rohrich, Rod J.; Savetsky, Ira L.; Suszynski, Thomas M.; Mohan, Raja; Avashia, Yash J.
Abstract : Summary: In an era with smartphone photography and social media (specifically, "selfies"), basal view aesthetics is becoming increasingly important. Achieving balance between the nasal base and the remainder of the nose and face while preserving or restoring external valve function are essential to a successful rhinoplasty. Without a systematic approach to the nasal base, it is more difficult to achieve an ideal outcome from both aesthetic and functional standpoints. This article outlines an organized and systematic approach to the nasal base, beginning with comprehensive nasofacial analysis. The authors continue by describing idealized basal view aesthetics and provide a treatment algorithm for common deformities that include alar flaring and a wide nasal base. The authors attempt to provide a comprehensive approach to the treatment of the nasal base by discussing the implications of treating columellar deformities, tip positioning, or alar-columellar discrepancies on the overall aesthetics of the lower third of the nose. Furthermore, technical considerations are given for common surgical maneuvers addressing the alar base to help guide treatment and prevent complications such as poor scarring, notching, nostril asymmetry or stenosis (external valve obstruction), and alar deformities ("parenthesis" or "bowling pin"), to name a few.